Pakistan : First Review Under the Stand-By Arrangement and Request for Waivers and Modification of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2001)
Pakistan showed great achievements under the program supported by the Stand-By Arrangement. Executive Directors stressed the need to implement strong fiscal, monetary, and exchange rate policies, and accelerate structural reforms. They emphasized the need for enhancing governance, rationalization of energy prices, broadening of tax base, strengthening of tax administration, and improving the financial position of public enterprises and banks. Directors agreed that the country has completed the first review under the Stand-By Arrangement, and approved a waiver.